2006
DOI: 10.1103/physrevb.74.205305
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy of Mn on Si(001): Adsorption, surface diffusion, and magnetic properties studied by density-functional theory

Abstract: Ultrathin films of manganese silicides on silicon are of relevance as a possible material system for building spintronics devices with silicon technology. In order to achieve insight into epitaxial growth of such films on Si͑001͒, total-energy calculations are presented using density-functional theory and the full-potential augmented plane wave plus local orbital method. For adsorption of a single Mn atom on Si͑001͒, we find that binding at the subsurface sites below the Si surface dimers is ϳ0.9 eV stronger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 36 publications
6
59
0
Order By: Relevance
“…20 In this study, Mn was found to be incorporated into Si as an interstitial dopant in good agreement with recent first-principles calculations. [23][24][25] The interstitial Mn was also observed in thin films irradiated by ultraviolet light releasing metal species into the semiconductor substrate. 26 Meanwhile, molecular beam epitaxy produces samples with mostly substitutional Mn in the Si matrix.…”
Section: Introductionmentioning
confidence: 91%
“…20 In this study, Mn was found to be incorporated into Si as an interstitial dopant in good agreement with recent first-principles calculations. [23][24][25] The interstitial Mn was also observed in thin films irradiated by ultraviolet light releasing metal species into the semiconductor substrate. 26 Meanwhile, molecular beam epitaxy produces samples with mostly substitutional Mn in the Si matrix.…”
Section: Introductionmentioning
confidence: 91%
“…In order to circumvent these problems we are investigating the feasibility of a surface-driven approach for the incorporation of Mn into a Si matrix. This approach has been suggested in several theoretical studies, which indicate that selected Mn-Si surface structures, and delta-doped layers of Mn embedded in Si might indeed be ferromagnetic [11,[16][17][18][19][20][21][22][23]. A set of recent STM studies has been geared towards the investigation of the formation of Mn surface structures on the Si(1 0 0) surface [18][19][20]24].…”
Section: Introductionmentioning
confidence: 99%
“…While DFT calculations 30 and scanning tunneling microscopy (STM) experiments 31 show that the subsurface sites are more favorable for Mn on Si(001), STM measurements on Mn deposited at room temperature show that Mn adatoms are energetically inhibited from populating these sites at room temperature and instead form chains on the surface. 32,33 By depositing the capping layer prior to annealing, we enabled interactions between the surface Mn layer and the deposited Si that leads to the formation of a MnSi-B20 phase.…”
Section: Xafs Experiments and Analysismentioning
confidence: 99%